Bribes and Bombs: The Effect of Corruption on Terrorism - Daniel Meierrieks; Daniel Auer (American Political Science Review, 2024)
We leverage plausibly exogenous variation in regional exposure to corruption to provide causal estimates of the impact of local political corruption on terrorist activity for a sample of 175 countries between 1970 and 2018. We find that higher levels of corruption lead to more terrorism. This result is robust to a variety of empirical modifications, including various ways in which we probe the validity of our instrumental variables approach. We also show that corruption adversely affects the provision of public goods and undermines counter-terrorism capacity. Thus, our empirical findings are consistent with predictions from a game-theoretical representation of terrorism, according to which corruption makes terrorism relatively more attractive compared to peaceful contestation, while also decreasing the costs of organizing and carrying out terrorist attacks.
Keywords: 320